Evaluación de conocimientos relacionados con cuidados paliativos en estudiantes y docentes de la carrera de Enfermería de la Universidad Nacional de Loja - Alvear Jumbo, Arianna Michelle (2025)
Ongoing and up-to-date training of nursing students and teachers directly influences the correct application of new and improved techniques and procedures in the evaluation and treatment of patients requiring palliative care. The purpose of the research was to determine the level of knowledge related to palliative care in students and teachers of the nursing program at the National University of Loja in the academic period October 2022 - February 2023; To characterize socio-demographically and identify the level of knowledge related to palliative care and design an educational proposal aimed at strengthening knowledge of palliative care in the Faculty of Human Health. It was set up as a quantitative, cross-sectional cohort study, made up of 109 participants, of which 92 were undergraduate students and 17 were teachers of the program, to whom the Palliative Care Knowledge questionnaire was applied. It was found that 78.90% (n=86) were women, aged 14 to 26 years, with 80.73% (n=88), single in 84.40% (n=92), and of mixed ethnicity in 98.17% (n=107). Regarding knowledge about palliative care, students showed a low level or little preparation with 58.70% (n=54) and in teachers a low level of knowledge predominated in the same way with 52.94% (n=9). The analysis showed that there is not a good level of knowledge related to palliative care among both undergraduate students and nursing teachers at the National University of Loja